Intervensi Senam untuk Meningkatkan Kualitas Tidur pada Lansia dengan Gangguan Tidur - Theresia Eriyani; Iwan Shalahuddin; Sandra Pebrianti; Indra Maulana; Devi Nurrahmawati (Universitas Malahayati Lampung, 2023)
ABSTRACT The elderly will experience physical, psychosocial and spiritual changes. One such change is a change in sleep quality. According to the National Sleep Foundation (NSF) about 67% of the 1,508 elderly in America aged 65 years and over reported having sleep disturbances and as many as 7.3% of the elderly complained of impaired initiation and maintaining sleep or insomnia. Sleep disturbances can cause disturbances in activities so that productivity decreases which often interfere with their activities. This study aims to determine the effect of gymnastics intervention in the elderly with insomnia on improving the quality of sleep of the elderly. This study used a scoping review method approach. The databases used in the search for related literature are Pubmed and ScienceDirect. Article searches are conducted using English keywords namely